Pengaruh Brand Ambassador, Brand Image Dan Brand Awareness Terhadap Minat Beli Konsumen Tokopedia (Studi Kasus Pada Mahasiswa FEB Unisma Angkatan 2018) - Juanda Chrystantor; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The aim of this study is to identify and evaluate the brand ambassadors, brand awareness, and brand image that simultaneously and in part impact Tokopedia customers' desire to purchase products. Buying interest is the dependent variable being measured, whereas brand ambassador, brand image, and brand awareness are the independent variables. Quantitative research using a descriptive methodology was used in this study. From the outset to the creation of the study design, the quantitative research method's specifications are systematic, well-planned, and clearly defined. The SPSS application was used to manage the data using multiple linear regression analysis. The information used includes both primary and secondary data that were gathered through surveys, interviews, and both direct and indirect observations. Since the sample size for this study is unclear, the Maholtra calculation with information on 15 indicators multiplied by 5 results in 75. Data processing revealed that the variables of brand ambassador, brand image, and brand awareness were present simultaneously and in part. Keyword: Purchase intention, Brand ambassador, Brand image, and Brand awarness.